Law regarding trawling activities in Malaysia / Ahmed Zaid Effendi Shamsul Bahri … [et al.] - Shamsul Bahri, Ahmed Zaid Effendi; Hanafi, Muhammad Nazmi; Ali, Siti Hajar; Roslan, Yazid Mustaqim (2014)
The main objective of this research is to improvise the law concerning trawling activities in Malaysia. As all of us aware, the division of the power regarding marine is stated under the Federal Constitution, so it will give more precise concept on how to govern this issue as the Federal Government has a power over fishermen under the Department of Fishery. The primary legislation with regard of trawling is the Fisheries Act and its subsidiary legislations which have more specific provisos on regulating trawling. The enforcement agency such as the Malaysian Maritime Enforcement Agency (MMEA) will be studied as well since the jurisdiction of power is necessarily to be discussed in order to give better pictures how authorities come up with approaches to curb illegal trawling issues within Malaysian waters. We also will cite legal and factual obstacles faced by them during their operation from. Besides, the research also will cover on the International Law of Sea like the United Nation of Law of Sea (UNCLOS) which had been ratified by Malaysia. This is crucial since the incorporation the International Law is a must once the country had ratified particular treaties and conventions hence giving effects towards our fisheries' laws. The increase of trawling in Malaysia also had been contributed from some factors like loose enforcement by authorities, licensing-procedurals, fisherman's ethical codes and non-abidance of certain regulations set up by the Department of Fisheries as had been roughly discussed in newspapers. To encounter all these weaknesses, in this research, we also provide the solutions that can be done in order to strengthen the integrity of authorities in enforcement and suggests a few of amendments to make the fisheries' law become more restrictive law.